Evgeny Gippius – the Researcher of the Musical Culture of the Belorussian Polesye - Tavlai, Galina V. (Music Scholarship / Problemy Muzykal’noj Nauki, 2013)
The article sheds light on the role of the classic of Russian ethnomusicology, Evgeny Gippius in the research of the song culture of the Belorussian Polesye. Attention is focused on the paths of formation of studies of folk music in Russia, the combined research activities of Evgeny Gippius and Zinaida Evald, and the individual features in the thinking of each of the representatives of that famous “musicological group.” Their research activities personify the ethnomusicologal work of the Russian Institute for History of the Arts in the 1920s and 1930s. Specification is given of Gippius’ analytical method, which gives primary role to: live observation, direct auditory perception, detailed research of the means of coordination of music and words, with consideration of the creative renewal of the subsequent strophes by the singers. All the aforementioned means of analytical work precede notation in their order of rank. The article validates the authorship of Gippius in formulating the scholarly category of “tune-formula” and sheds light on the sources of Zinnaida Evald’s interest in the auditory peculiarity of the melodies from Polesye. Keywords: folk music of the Belorussian Polesye, Evgeny Gippius, Zinaida Evald, ethnography, tune-formula